Clinical and Trichoscopy Features in Trichorhinophalangeal Syndrome: A Multicenter Retrospective Study - Melo, Daniel Fernandes; Rita Fernanda Cortez de Almeida; Carla Jorge Machado; Marcela Benez; Pedro da Rocha Andrade Neto; Andre Donda; Isabela Peron Melhado; Rogerio Nabor Kondo; Sidney Frattini; Giselle Pinto; Aline Donati (Dermatology Practical & Conceptual, 2025)
Introduction: Trichorhinophalangeal syndrome (TRPS) is a rare autosomal dominant genetic disorder, characterized by trichological, craniofacial, and skeletal abnormalities. To date, limited data is available on hair involvement in TRPS, especially those focusing on trichoscopy. Objective: We aimed to describe the epidemiology and clinical and trichoscopy features of TRPS.Methods: We performed a retrospective multicentric study using chart review and images from 6 patients with a confirmed diagnosis of TRPS. Hair density (hair/field; field 13´1.4 mm) was classified into high (>30), medium (21-30), low (11-20), very low (5-10) hair density, and hairless (<4) categories.Results: Most patients were females with a median age of 12 at diagnosis. Hair density ranged from very low to medium. All female patients presented a high occipital hairline. Our patients had exclusively non-terminal hairs and no cases with high hair density, following the literature that describes thin and sparse hairs. Hair density was related to a higher proportion of single hair units, while the distance between follicles was within normal limits.Conclusion: This case series focused on the trichoscopy features of this condition, detailing aspects of the distance between shafts, hair density, and hair thickness. The results presented challenged previously published features of the syndrome.